2021
DOI: 10.5334/gh.916
|View full text |Cite
|
Sign up to set email alerts
|

QT Interval Monitoring with Handheld Heart Rhythm ECG Device in COVID-19 Patients

Abstract: Background: QTc prolongation is an adverse effect of COVID-19 therapies. The use of a handheld device in this scenario has not been addressed. Objectives: To evaluate the feasibility of QTc monitoring with a smart device in COVID-19 patients receiving QTc-interfering therapies. Methods: Prospective study of consecutive COVID-19 patients treated with hydroxychloroquine ± azithromycin ± lopinavir-ritonavir. ECG monitoring was performed with 12-lead ECG or with KardiaMobile-6L. Both registries were also sequentia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…It was demonstrated that the KM-1l device has adequate precision and agreement compared to the standard 12-lead ECG. Minquito-Carazo et al ( 25 ) evaluated the feasibility of QTc monitoring with KardiaMobile 6L in 63 COVID-19 patients receiving therapies that could interfere with the QT interval. QTc could be measured in lead II in 84.5% of the registries.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that the KM-1l device has adequate precision and agreement compared to the standard 12-lead ECG. Minquito-Carazo et al ( 25 ) evaluated the feasibility of QTc monitoring with KardiaMobile 6L in 63 COVID-19 patients receiving therapies that could interfere with the QT interval. QTc could be measured in lead II in 84.5% of the registries.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the global pandemic further complicated cardiology services as COVID-19 eventually emerged as an airborne disease, and physical distancing had been carried out to prevent the spread of infection. Therefore, attempts were made to use portable ECG devices to minimize exposure and disease transmission [ 18 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…15 Chapter 4 Systematic review results t he literature searches of bibliographic databases conducted for this EVA systematic review, including additional scoping searches conducted to identify costs and cost-effectiveness studies, identified 8505 unique references. After initial screening of titles and abstracts, 28 references were considered to be potentially relevant and ordered for full paper screening; of these 10 publications, 26,31,34,37,[39][40][41][42][43] relating to six studies, were included in the review. A further three publications, one provided by NICE/ Specialist Committee Members (SCMs) 14 and two provided by the manufacturer of KardiaMobile 6L, AliveCor, 51,52 were assessed and included in the review.…”
Section: Methods Of Analysis/synthesismentioning
confidence: 99%
“…Based on the searches and inclusion screening described above, 13 publications, 14,26,31,34,37,[39][40][41][42][43]51,52 relating to 8 studies, and 2 additional unpublished reports, 53,54 were included in this review; the results section of this report cites studies using the primary publication only.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%